2019
DOI: 10.15421/2019_104
|View full text |Cite
|
Sign up to set email alerts
|

Factors influeincing health tourism development in Belokurikha Resort

Abstract: The paper studies approaches to understanding the health tourism in Belokurikha Resort. In fact, Belokurikha Resort is the largest recreational area in the Asian part of the Russian Federation. The authors define the factors of tourism development in the area and outline the elements of health tourism development: historical development, natural resources, economic, infrastructural, ethno-social, tourist, administrative, informational and business ones. The paper considers an influence of these factors on sust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
0
0
3
Order By: Relevance
“…Любителям зимних видов спорта открываются широкие возможности для катания на горнолыжных склонах [2,7].…”
Section: результаты исследованияunclassified
See 2 more Smart Citations
“…Любителям зимних видов спорта открываются широкие возможности для катания на горнолыжных склонах [2,7].…”
Section: результаты исследованияunclassified
“…Таким образом, территориальные туристские комплексы являются важнейшим инструментом развития туризма в России. Пространственное планирование, как в случае с курортом Белокуриха и окрестностями, позволяет оптимизировать использование туристских ресурсов, совершенствовать инфраструктуру и обеспечивать устойчивое развитие туристских территорий [2].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Ullah et al argued that the development of a new form of health and wellness tourism depends on the demand and supply of the tourist market and related industries, infrastructure, and external environments [17]. Taking Russia as an example, Dunets et al concluded that social history, natural resources, economy, infrastructure, ethnic groups, tourism conditions, policies, and the Internet are components of the sustainable development of rural health and wellness tourism [18]. In rural health and wellness tourism activities, familiarization with traditional rural and farming cultures and experiencing the natural environment can meet the tourists' different emotional needs and benefit physical and mental health.…”
Section: Health and Wellness Tourism Researchmentioning
confidence: 99%